PENGARUH PENGETAHUAN TERHADAP PERILAKU MEROKOK PADA SISWA PUTRA KELAS XI DI SMK JAGARA KECAMATAN DARMA KABUPATEN KUNINGAN TAHUN 2019 - Suryadi, Yadi (Kos Globalindo Group, 2021)
This research is backed by a thought that now there is an increase in the active smoker on the teenager (aged 15-19 years) that is from 5% to 17% (Depkes, 2013). All of the health expert have been concluded that in health, smoking would give the negative effect, especially for their children. Now smoking in the teenagers (aged 15-19) or same as SMA/SMK is a behavior that is very easy to be founded. All of the health expert have been concluded that in health, smoking would give the negative effect, especially for their children. Now smoking in the teenagers (aged 15-19) or same as SMA/SMK is a behavior that is very easy to be founded. Teen smoker in public places and not infrequently they are smoking by using uniform and are close with the school. One of the factor that affects the behavior smoking is low of knowledge The purpose of this research is to know the knowledge and the smoking behavior of students in the XI grade men students at SMK JAGARA. The type of this research is quantitative research with the design of descriptive analysis design correlation with cross sectional approaches. The sample of this research is 70 students of XI grade son in SMK JAGARA. With saturation sampling method. Retrieval of quantitative data is by giving quessionnaires. The tests conducted by validity test shows that all of data are valid, then reliability test shows that variable X (0.832) and variable Y (0.713) so it’s reliable. The linearity test can be known that the value is contstant as much as 50.607 and X is 0.509 then it’s in direct because there is the influence between variable X and variable Y, normality test of variable X obtained the signify value as much as 0.341 and variable Y as much as 0.427 where all of them are normally distributed, then the hyphothesis test shows that Ha is accepted and Ho is rejected with the result shows the percentage of the influence of knowledge towards smoking behaior as much as 46,6%. Description analysis shows that student’s knowledge is high and smoking behavior is moderate. It’s would be concluded that there’s the influence of knowledge towards smoking behavior.